Identification and characterization of thorny and high temperature tolerant brinjal (Solanum melongena) genotype for hot arid environment - VERMA, A K; SAMADIA, D K; RAM, HANUMAN; RAM, CHET; KUMAR, P (The Indian Journal of Agricultural Sciences, 2024)
Brinjal (Solanum melongena L.) is one of the most common vegetable which is generally cultivated as rainy (kharif) season crop to get the fruits during autumn-winter season. However, the summer season crop has more potential than the kharif season as the fruits harvested during summer gets premium price in the market. But, getting high quality fruit yield during summer due to high temperature stress (>45°C) is a challenge particularly in hot arid agro-climate as the day and night temperature above 35°C reduces the pollen viability, fruit set, number of fruits/plant and colour retention to a great extent. The present study was carried out during 2020 and 2021 at ICAR-Central Institute of Arid Horticulture, Bikaner, Rajasthan to develop varieties with better quality fruit yield under high temperature conditions. The experiments were conducted in split plot design (SPD) considering environments as main plots and replicates within environment as subplots with three replications. As a result, CIAH-22 has been identified and characterized as a trait specific high temperature tolerant (up to 45°C) thorny brinjal genotype suitable for hot arid region. Fruit weight at marketable stage varied from 144.56–155.84 g that indicates bigger sized fruits with thorns on calyx which are preferred most by the local growers and consumers of this region. It has the yield potential of 2.18–3.72 kg fruits/plant and 447.78–471.74 q/ha. The identified genotype CIAH-22 was able to set fruits at temperature as high as 45°C which was also evidenced by its pollen viability i.e. 83.71%. High pollen viability significantly enhanced fruit set, fruit weight and number of fruits per plant and thereby yield under high temperature stress. Thus, this identified genotype can be a potential source for brinjal improvement for high temperature tolerance and regional preference of big-sized thorny fruits with attractive colour retention.